„Children’ s education must be taken care of” - Farkas, K., Claudia (Knowledge Management, 2024)
Childhood studies aim to explore the past of childhood, making the life and circumstances of the child the subject of scientific research. The examination of educational institutions plays an essential role in the process of learning about childhood (Szabolcs, 2011), which are also an integral part of the mediating system of children’s culture (Bús, 2013). The aim of this study is to extend the knowledge about childhood in the so-called socialist period, more specifically, the reflection on the life and culture of children in elementary education in Hungary in the first half of the 1970s, based on the analysis of the issues of the pedagogical journal „A Tanító” from 1970 to 1975. The research seeks to answer the question of whether there were areas of culture and education that were prioritised by the school, which sphere was given priority and what were the pedagogical aims and characteristics of each. The topic is novel, there is little information available on the problem raised for the given era. The study is based on primary („A Tanító” journal) and secondary sources, is methodologically qualitative, deductive, exploratory and explanatory, and uses the method of documentary analysis. It was found that, during the period under study, the school’s priority was children’s literacy and artistic education, which were implemented on several levels, through the mediation of children’s culture, and by incorporating new methods and new approaches. „Youth as readers” was not only a pedagogical aim but also a social one. The artistic formation of children’s tastes has taken many forms, and its role in building character and understanding the world around them has been recognised. The study broadens the framework for interpreting the history of childhood in the socialist period, offers new lessons and familiarizes you with educational methods of the time, which can be further considered in the present.